Analysis of Material and Energy Effects of Tofu Industry on Environmental Quality Using OpenLCA 1.103 Software (Case Study: Sari Murni Tofu Factory, Kampung Krajan, Mojosongo, Surakarta, Central Java, Indonesia) - Elvis Umbu Lolo; Agerippa Yanuranda Krismani; Cicik Sudaryantingsih; Richardus Indra Gunawan; Yonathan Suryo Pambudi; Widianto; Alfred Dedu Ngalung (PT FORMOSA CENDEKIA GLOBAL, 2023)
The problem faced by the tofu industry is waste management. So efforts need to be made so that the waste does not cause pollution. One of them is identifying the components of environmental pollution using the life cycle assessment principle with the open LCA application. The results of this study are divided into five impact categories, namely, abiotic depletion potential which mainly affected by soybean production of 0.263 kg of antimony and a direct contribution based on the Sankey diagram of 85.953%. Land competition is influenced by soybean production of 1148 m2a and a direct contribution of 99.982%. The depletion of the ozone layer is affected by the energy of 0.000719 kg of CFC-11 and the direct contribution of 76.468%.